Feasibility of a geriatric comanagement (GERICO) pilot program for patients 75 and older undergoing radical cystectomy. Issue 6 (June 2022) - Letica-Kriegel, Allison S.; Tin, Amy L.; Nash, Garrett M.; Benfante, Nicole E.; McNeil, Nita; Vickers, Andrew J.; Bochner, Bernard; Donat, Sherri M.; Goh, Alvin; Dalbagni, Guido; Donahue, Timothy; Cha, Eugene K.; et al.
Abstract: Background: Retrospective studies have shown the beneficial impact of geriatric comanagement (GERICO) on perioperative outcomes of older adults with cancer. We prospectively assessed the feasibility of perioperative GERICO for older adults with bladder cancer undergoing radical cystectomy. Methods: We conducted a pilot study wherein all patients 75 years and older undergoing radical cystectomy between October 2019 and November 2020 were referred to the Geriatric Service preoperatively. Feasibility was defined according to the percentage of patients who received preoperative evaluation by the Geriatrics Service, who were followed for more than 80% of their inpatient days and who had their surgery rescheduled for logistical reasons. Urology advanced practice provider (APP) satisfaction with the program was measured via an 11-item survey. Results: Sixty-six eligible patients underwent radical cystectomy in the stated time frame; 59 (89%; 95% confidence interval [CI], 79–97%) were referred to the Geriatric Service for evaluation. The median age of patients who had geriatric comanagement was 79 years; 40 (68%) were male. Forty-one patients (69%) were visited on at least 80% of the days in which they were not in the intensive care unit. No surgeries were rescheduled for logistical reasons. Nine of the 12 urology APPs (75%) responded to the survey; all nine "somewhat" or "strongly" agreed with statements indicating satisfaction with the program. Conclusion: Despite the challenges of the COVID-19 pandemic, we showed that perioperative GERICO is feasible. Fully powered prospective randomized controlled trials should be conducted to assess GERICO's impact on perioperative outcomes of older adults with cancer.